Comparative investigations of in vitro and in vivo bioactivity of titanium vs. Ti–24Nb–4Zr–8Sn alloy before and after sandblasting and acid etching. Issue 40 (22nd June 2020) - Liu, Xin; Niu, Yumei; Xie, Weili; Wei, Daqing; Du, Qing
Abstract : To avoid the failure of clinical surgery due to "stress shielding" and the loosening of an implant, a new type of alloy, Ti–24Nb–4Zr–8Sn (TNZS), with a low Young's modulus acted as a new implant material in this work. Abstract : To avoid the failure of clinical surgery due to "stress shielding" and the loosening of an implant, a new type of alloy, Ti–24Nb–4Zr–8Sn (TNZS), with a low Young's modulus acted as a new implant material in this work. Meanwhile, the surface characteristics, MC3T3-E1 cell behavior and in vivo osseointegration of the titanium and TNZS before and after sandblasting and acid etching were studied comparatively. TNZS and Ti had the same microstructure based on the transmission electron microscopy results. Meanwhile, the TNZS alloy had a lower Young's modulus and surface nanohardness compared with pure titanium. However, the corrosion resistance of Ti was better than that of the TNZS sample in simulated body fluid solution. In addition, the TNZS alloy after sandblasting and acid etching (SLATNZS) had excellent cell adhesion, proliferation, differentiation, ALP activity and in vivo osseointegration ability such as there being almost no soft tissue as compared with other implants. Based on the current results, the new type of Ti–24Nb–4Zr–8Sn alloy showed good potential and promising application prospects in its biochemical aspects.